Immobilization of TiO2 on transparent plastic and its application in photocatalytic wastewater treatment. (February 2019) - Utami, F D; Rahman, D Y; Sustini, Euis; Abdullah, M
Abstract: A simple spray-coating method of immobilized TiO2 particles on the transparent plastic has been successfully applied in a photocatalytic wastewater treatment process. This method was initiated with a coating of adhesive polymer on plastic using doctor blade technique followed then by a spray-coating process of titania. The photocatalytic activity of the TiO2 -coated plastic sheets were tested with the decomposition of Methylene Blue (MB) under solar exposure. Eight layers of the coated sheets have the most powerful degradation effect of about 99% after 6 hours of irradiation. The reusability of the titania coating has also been investigated and still has a powerful photodecomposition ability of removing 98% of the MB compound.